Book Review: Teaching and Learning Writing in ESL/EFL, Foreign Language Teaching and Research Press, 2021 - Ha Thi Phuong Pham (Studies in Self-Access Learning Journal, 2024)
This article reviews the volume Teaching and Learning Writing in ESL/EFL by Rachael Ruegg, edited by Peter Yongqi Gu and Guoxing Yu, and published in 2021 by Foreign Language Teaching and Research Press, Beijing. The book provides a comprehensive overview of writing instruction, particularly within the EFL context, and addresses topics that practically-minded readers would expect, such as writing pedagogies, feedback, and assessment. This review explores these aspects in detail and reflects on the book’s strengths and weaknesses, offering suggestions on how the book could be utilised effectively.